Sustained censorship in IR (2023-01) (Iran) - Voidly (Voidly Global Censorship Index, 2023)
CRITICAL severity censorship detected in Iran. Data sourced from OONI.
Censorship Incident ID: IR-2023-0007. Severity: critical. Confidence: 75%